2016
DOI: 10.1007/s12551-016-0211-0
|View full text |Cite
|
Sign up to set email alerts
|

Supercoiling biases the formation of loops involved in gene regulation

Abstract: The function of DNA as a repository of genetic information is well-known. The post-genomic effort is to understand how this information-containing filament is chaperoned to manage its compaction and topological states. Indeed, the activities of enzymes that transcribe, replicate, or repair DNA are regulated to a large degree by access. Proteins that act at a distance along the filament by binding at one site and contacting another site, perhaps as part of a bigger complex, create loops that constitute topologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 83 publications
0
9
0
Order By: Relevance
“…Importantly, plectonemes spatially juxtapose sites that are distant in linear DNA sequence and, therefore, enable bridging and looping of DNA by proteins that engage multiple binding sites. Proteininduced conformational changes and separation of topological domains in DNA, in turn, provide another critical level of genomic regulation (6,(9)(10)(11)(12)(13)(14). A large body of experimental and computational research has resulted in a quantitative understanding of the average geometry of supercoiled DNA under a range of environmental conditions (7,(14)(15)(16)(17)(18)(19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…Importantly, plectonemes spatially juxtapose sites that are distant in linear DNA sequence and, therefore, enable bridging and looping of DNA by proteins that engage multiple binding sites. Proteininduced conformational changes and separation of topological domains in DNA, in turn, provide another critical level of genomic regulation (6,(9)(10)(11)(12)(13)(14). A large body of experimental and computational research has resulted in a quantitative understanding of the average geometry of supercoiled DNA under a range of environmental conditions (7,(14)(15)(16)(17)(18)(19)(20)(21)(22).…”
Section: Introductionmentioning
confidence: 99%
“…7,8 Writing ΔWr occurs in the form of plectonemes, an interwound con-formation of double-helical DNA, which enhances the target search of site-specific DNA-binding proteins 9 as well as protein-mediated loop formation. 10 Thus, organizing the genome in topological domains infers regulatory control over gene expression via DNA supercoiling. Consequently, the properties of DNA supercoiling have been intensively studied.…”
mentioning
confidence: 99%
“…DNA is supercoiled when Lk differs from the energetically most favorable value Lk 0 and the linking difference Δ Lk = Lk – Lk 0 can be expressed in terms of deviations in twist Δ T w and writhe Δ Wr from their equilibrium values (Δ Lk = Δ Tw + Δ Wr ). Twist deformations Δ T w affect formation of melting bubbles, cruciform, or Z-DNA and can modulate protein binding. , Writing Δ Wr occurs in the form of plectonemes, an interwound conformation of double-helical DNA, which enhances the target search of site-specific DNA-binding proteins as well as protein-mediated loop formation . Thus, organizing the genome in topological domains infers regulatory control over gene expression via DNA supercoiling.…”
mentioning
confidence: 99%
“…In addition, RNAP pausing at obstacles depends not only on the amplitude, but also on the directionality of the tension applied to the DNA template. Finally, she showed that the strength of a protein roadblock is increased if the protein bridges two distant sites, thus mediating a DNA loop (Finzi and Dunlap, 2016). In conclusion, looping might convert a weak protein-binding site into a strong roadblock for transcription, indicating new means of transcription regulation.…”
Section: Dna Mechanicsmentioning
confidence: 98%